2020
DOI: 10.1126/sciadv.aaz3327
|View full text |Cite
|
Sign up to set email alerts
|

The Mgs1/WRNIP1 ATPase is required to prevent a recombination salvage pathway at damaged replication forks

Abstract: DNA damage tolerance (DDT) is crucial for genome integrity maintenance. DDT is mainly carried out by template switch recombination, an error-free mode of overcoming DNA lesions, or translesion DNA synthesis, which is error-prone. Here, we investigated the role of Mgs1/WRNIP1 in modulating DDT. Using budding yeast, we found that elimination of Mgs1 in cells lacking Rad5, an essential protein for DDT, activates an alternative mode of DNA damage bypass, driven by recombination, which allows chromosome replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
(123 reference statements)
0
13
0
1
Order By: Relevance
“…These findings, in turn, raise the question of how template switch-mediated recombination is specifically facilitated but, in spite of Srs2 antirecombinase being counteracted, other modes of recombination that could be potentially dangerous for genome stability are inhibited at damaged forks. We addressed this question and found that Mgs1, an evolutionarily conserved AAA + ATPase (WRNIP1 in mammalian cells, RarA/MgsA in bacteria) (Hishida et al, 2001 ), contributes to preventing unwanted recombination at damaged and stalled replication forks (Jiménez-Martín et al 2020 ).…”
Section: Mgs1-dependent Inhibition Of a Salvage Pathway Of Recombinatmentioning
confidence: 99%
See 4 more Smart Citations
“…These findings, in turn, raise the question of how template switch-mediated recombination is specifically facilitated but, in spite of Srs2 antirecombinase being counteracted, other modes of recombination that could be potentially dangerous for genome stability are inhibited at damaged forks. We addressed this question and found that Mgs1, an evolutionarily conserved AAA + ATPase (WRNIP1 in mammalian cells, RarA/MgsA in bacteria) (Hishida et al, 2001 ), contributes to preventing unwanted recombination at damaged and stalled replication forks (Jiménez-Martín et al 2020 ).…”
Section: Mgs1-dependent Inhibition Of a Salvage Pathway Of Recombinatmentioning
confidence: 99%
“…We found that elimination of Mgs1 or its ATPase activity suppresses the high sensitivity of Rad5-deficient cells to MMS or hydroxyurea (HU). A likely explanation for this suppression is the observation that in cells lacking Rad5, the absence of Mgs1 facilitates an alternative pathway of DNA damage bypass that allows overcoming of MMS-induced DNA lesions and the completion of chromosome replication (Jiménez-Martín et al 2020 ) (Fig. 1 ).…”
Section: Mgs1-dependent Inhibition Of a Salvage Pathway Of Recombinatmentioning
confidence: 99%
See 3 more Smart Citations